Potential Precursor Alternatives to the Pyrophoric Trimethylaluminium for the Atomic Layer Deposition of Aluminium Oxide. Issue 31 (26th April 2019) - Mai, Lukas; Boysen, Nils; Zanders, David; de los Arcos, Teresa; Mitschker, Felix; Mallick, Bert; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana
Abstract: New precursor chemistries for the atomic layer deposition (ALD) of aluminium oxide are reported as potential alternatives to the pyrophoric trimethylaluminium (TMA) which is to date a widely used Al precursor. Combining the high reactivity of aluminium alkyls employing the 3‐(dimethylamino)propyl (DMP) ligand with thermally stable amide ligands yielded three new heteroleptic, non‐pyrophoric compounds [Al(NMe2 )2 (DMP)] (2 ), [Al(NEt2 )2 (DMP)] (3, BDEADA) and [Al(N i Pr2 )2 (DMP)] (4 ), which combine the properties of both ligand systems. The compounds were synthesized and thoroughly chemically characterized, showing the intramolecular stabilization of the DMP ligand as well as only reactive Al−C and Al−N bonds, which are the key factors for the thermal stability accompanied by a sufficient reactivity, both being crucial for ALD precursors. Upon rational variation of the amide alkyl chains, tunable and high evaporation rates accompanied by thermal stability were found, as revealed by thermal evaluation. In addition, a new and promising plasma enhanced (PE)ALD process using BDEADA and oxygen plasma in a wide temperature range from 60 to 220 °C is reported and compared to that of a modified variation of the TMA, namely [AlMe2 (DMP)] (DMAD). The resulting Al2 O3 layers are of high density, smooth, uniform, and of high purity. The applicability of the Al2 O3 films as effective gas barrier layers (GBLs) was successfully demonstrated, considering that coating on polyethylene terephthalate (PET) substrates yielded very good oxygen transmission rates (OTR) with an improvement factor of 86 for a 15 nm film by using DMAD and a factor of 25 for a film thickness of just 5 nm by using BDEDA compared to bare PET substrates. All these film attributes are of the same quality as those obtained for the industrial precursor TMA, rendering the new precursors safe and potential alternatives to TMA. Abstract : Replacing trimethylaluminium : An intramolecular stabilized aluminium precursor class was designed to substitute the industrial used trimethylaluminium in low‐temperature plasma‐enhanced atomic layer deposition processes.